Graduate School Management Characteristics to Ensure Production of Quality Graduates for Sustainable Competitiveness - Kranravee Komoldit; Malai Tawisook; Nataya Pilanthananond (My University, 2018)
Abstract With modern society impacted by globalization, declining birth rates and technological advancement, higher education institutions struggle to produce graduates ready to enter the workforce in adequate quality and number in an increasingly competitive atmosphere. In countries such as Thailand, outdated instruction and social inequalities add further complication. This study aims to examine the management characteristics of such institutions that will effectively promote graduate production and competitiveness in the digital era. Data was collected using Ethnographic Delphi Future Research, with interviews and questionnaires conducted with specialists in the fields of education and management. Results from information gathered and analyzed underline the necessity for supplementing graduate education with information systems technology and digital resources and aligning curricula and practices to meet the demands of industries in need of future manpower. The research identified mechanisms and policies with which higher education management can encourage new knowledge creation through research and provide accessible and convenient avenues for learning to enhance institutional competitiveness and help shape improved, intelligent, better qualified and more marketable human resources for future generations.
Keywords: Delphi Method; Higher Education Governance and Development